Creative Multilingualism (Open Book Publishers, 2020)
Multilingualism is integral to the human condition. Hinging on the concept of Creative Multilingualism – the idea that language diversity and creativity are mutually enriching – this timely and thought-provoking volume shows how the concept provides a matrix for experimentation with ideas, approaches and methods.